THE RELATIONSHIP OF WORK DISCIPLINE, EMOTIONAL INTELLIGENCE, LEADERSHIP AND THE PERFORMANCE OF PAI HIGH SCHOOL TEACHERS IN PADANG CITY - Slamet Riyadi; Nur Adilah; Suwardi (Journal of Social and Economics Research, 2023)
This research aims to prove the influence of work discipline, emotional intelligence and leadership style on teacher performance PAI teacher at SMAN Padang City. The sample in this research was all teachers PAI teacher at SMAN Padang City, totaling 53 people. The type of data used is primary data, namely through distributing questionnaires. To analyze the influence of work discipline, emotional intelligence and leadership style on teacher performance PAI teacher at SMAN Padang City, using multiple regression. From the results of hypothesis testing that has been carried out, it can be concluded that work discipline does not have a significant effect on teacher performance PAI teacher at SMAN Padang City. Emotional intelligence has a significant effect on teacher performance PAI teacher at SMAN Padang City. Meanwhile, leadership style does not have a significant effect on teacher performance PAI teacher at SMAN Padang City.